(Morpho)syntactic comprehension in agrammatic aphasia : Evidence from Greek - Fyndanis, Valantis; Varlokosta, Spyridoula; Tsapkini, K (My University, 2013)
Background: A number of hypotheses have been formulated to account for comprehension data in agrammatic aphasia. They explain deficits in comprehending specific structures, such as semantically reversible non-canonical sentences, for example, Trace Deletion Hypothesis (TDH, Grodzinsky, 1986, 1990, 1995), or functional categories, for example, Tree Pruning Hypothesis (TPH, e.g., Friedmann, 2006); Tense Underspecification Hypothesis (TUH, Wenzlaff & Clahsen, 2004, 2005); Interpretable Features' Impairment Hypothesis (IFIH; e.g., Varlokosta et al., 2006). Several studies, however, report evidence contradicting these theories (e.g., Caramazza, Capasso, Capitani, & Miceli, 2005; Dickey, Milman, & Thompson, 2008) and propose new accounts to explain the comprehension deficits in agrammatic aphasia, for example, Distributed Morphology Account (DMA, Dickey et al., 2008). Aims: Against the background above, this study investigates the ability of three Greek-speaking agrammatic individuals to comprehend a wide range of structures and functional categories: semantically reversible (canonical) active and (non-canonical) passive sentences, Complementizer Phrase, subject-verb Agreement, Tense, and Aspect. Methods & Procedures: We administered: (a) two sentence-picture matching tasks to test comprehension of reversible active and passive sentences, and Tense; (b) a sentence grammaticality judgement task to test judgement of Tense, Aspect, and subject-verb Agreement; and (c) a picture-pointing task to test comprehension of Complementizer Phrase. Outcomes & Results: (a) Two of the three agrammatic participants performed at chance on reversible passive sentences and above chance on active sentences. The third participant performed equally high on the two sentence types. Two participants performed at chance on Tense comprehension and one above chance. (b) The three participants were selectively or across-the-board impaired in judgement of Agreement, Tense, and Aspect. One of the two selectively affected participants had chance performance on Aspect and above chance performance on Agreement and Tense. The other one performed at chance on Aspect and Tense, and above chance on Agreement. The third participant's performance was equally poor on all three categories. (c) All three agrammatic participants performed above chance on the comprehension of Complementizer Phrase. Conclusions: In comprehension/judgement, canonical and non-canonical sentences do not dissociate in all agrammatic speakers, while functional categories associated with the verb morphology may be compromised in the face of relatively well-preserved categories that are located higher in the syntactic hierarchy. All three agrammatic participants support the DMA, and two of them support the TDH. Instead, none of them provided support to the TPH, TUH, and IFIH. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: Aphasia; Grammaticality judgement; Agrammatism; Comprehension; Functional categories; Greek